Faecal-wood biomass co-combustion and ash composition analysis. (1st September 2017) - Somorin, Tosin Onabanjo; Kolios, Athanasios J.; Parker, Alison; McAdam, Ewan; Williams, Leon; Tyrrel, Sean
Highlights: Co-combustion analysis was investigated using a bench-scale combustor test rig. Raw human faeces (FC) contained 73.9 ± 4.4 wt% moisture as received basis. Blending with wood dust (WD) in a 50:50 ratio reduced moisture levels by ∼40%. Minimum acceptable blend for combustion without prior drying is 30:70 WD:FC. Fuel burn rates are 3.18–4.49 g/min for all the blends at air flow of 12–18 L/min. Oxygen, potassium and calcium are the most abundant elements in faecal ash. Abstract: Fuel blending is a widely used approach in biomass combustion, particularly for feedstocks with low calorific value and high moisture content. In on-site sanitation technologies, fuel blending is proposed as a pre-treatment requirement to reduce moisture levels and improve the physiochemical properties of raw faeces prior to drying. This study investigates the co-combustion performance of wood dust: raw human faeces blends at varying air-to-fuel ratios in a bench-scale combustor test rig. It concludes with ash composition analyses and discusses their potential application and related problems. The study shows that a 50:50 wood dust (WD): raw human faeces (FC) can reduce moisture levels in raw human faeces by ∼40% prior to drying. The minimum acceptable blend for treating moist faeces without prior drying at a combustion air flow rate of 14–18 L/min is 30:70 WD: FC. For self-sustained ignition and flame propagation, the minimum combustion temperature required for conversion of the fuel to ash is ∼400 °C. The most abundant elements in faecal ash are potassium and calcium, while elements such as nickel, aluminium and iron are in trace quantities. This suggests the potential use of faecal ash as a soil conditioner, but increases the tendency for fly ash formation and sintering problems.